Vitamin D and its association with severity and control of childhood bronchial asthma - Kamalakshi G Bhat; Soundarya Mahalingam; V C Soumya (Wolters Kluwer Medknow Publications, 2023)
Background: Bronchial asthma is a common disease in childhood. Vitamin D deficiency is a common unidentified nutritional deficiency. In spite of high prevalence, an association between the two has not been well understood. Objectives: Our study aimed to determine serum Vitamin D levels among asthmatic children and its association with clinical severity and level of control. Methods: A hospital-based cross-sectional study was conducted from 2017 to 2019 where 64 recurrent wheezers, classified into 6-15 years and the under 5 wheezers as per Global Initiative for Asthma guidelines, were included. The group of asthmatic children was comparable with respect to their demographic profiles with good adherence and proper inhaler use. Serum Vitamin D levels were estimated using an enzyme-linked immunosorbent assay and classified using the US Endocrine Society classification. Association between Vitamin D status and outcome variables was analyzed using Chi-square test, Fisher's exact test, unpaired t-test, and ANOVA. Results: Among the 64 wheezers, 29 (45.3%) had intermittent symptoms and 35 (54.7%) had persistent symptoms. Mean Vitamin D levels in the entire study population were in deficiency range (18.96 ng/ml ± 2.23). Persistent asthmatics had significantly lower Vitamin D levels (13.75 ng/ml) as compared to intermittent asthmatics (28.52 ng/ml). Those asthmatics who had hypovitaminosis D had higher rates of hospitalization (P = 0.048), increased use of rescue medications (P = 0.008), and poor symptom control (P = 0.001). Conclusions: Asthmatic children had a higher incidence of reduced Vitamin D levels showing a statistically significant association. There is also a significant association between Vitamin D level and poor symptom control, hospitalization for exacerbations, and requirement of rescue medication in asthmatic children.